Enterovirus Infection Restricts Long Interspersed Element 1 Retrotransposition - Li, Yan; Shen, Siyu; Guo, Haoran; Zhang, Zhe; Zhang, Lili; Yang, Qingran; Gao, Yanhang; Niu, Junqi; Wei, Wei (Frontiers in Microbiology, 2021)
Long interspersed element 1 (LINE-1 or L1) is the only active autonomous retrotransposon in the human genome that can serve as an endogenous upstream activator of cytoplasmic nucleic acid sensing pathways to elicit an antiviral immune response. In this study, we investigated the influence of enteroviral infection on L1 mobility. The results showed that infection with different enteroviruses, both EV-D68 and EV-A71, blocked L1 transposition. We screened diverse viral accessory proteins for L1 activity and identified EV-D68 2A, 3A, 3C, and EV-A71 ORF2p proteins as viral L1 inhibitors. EV-D68 2A suppressed L1 mobility by translational suppression of L1 proteins. Viral proteins 3A and 3C restricted ORF2p-mediated L1 reverse transcription in isolated L1 ribonucleoproteins. The newly identified enteroviral protein ORF2p inhibited the accumulation of intracellular L1 ORF1p. Altogether, our findings shed light on the strict modulation of L1 retrotransposons during enterovirus replication.